The Association Between Endometriosis Treatments and Depression and/or Anxiety in a Population-Based Pathologically Confirmed Cohort of People with Endometriosis - Emma Goodwin; Helena Abreu do Valle; Amanda Nitschke; Joseph Puyat; Paul J. Yong; Gillian E. Hanley (Mary Ann Liebert, 2023)
Objective: Endometriosis patients have a high rate of co-occurring anxiety and depression. There is currently no literature investigating how this may affect endometriosis treatment and outcomes. This study examines the prevalence of depression and anxiety in a pathologically confirmed population-based endometriosis cohort and examines how endometriosis treatments and outcomes differ by the presence of co-occurring depression and/or anxiety. Methods: This retrospective cohort study using population-based administrative data sets included pathologically confirmed endometriosis patients identified from the complete pathology records of Vancouver Coastal Health Authority (British Columbia, Canada) between 2000 and 2008. These data were linked with population-based health data for follow-up to 2017. Bivariate analyses assessed differences between patients with depression and/or anxiety and those without. Odds ratios (ORs) were calculated to assess the odds of binary postsurgical outcomes. Results: Our final cohort consisted of 3815 patients. There were 603 patients (15.8%) with depression and/or anxiety. They were more likely to visit a physician for pelvic pain, more likely to take some hormonal medications, and more likely to fill prescription-level analgesics, including opioids both before and after surgery. They also had a significantly higher risk of reoperation for their endometriosis than people without co-occurring depression and/or anxiety (OR 1.32, 95% confidence interval [CI]: 1.07?1.61). Conclusion: Endometriosis patients with co-occurring depression and/or anxiety used more health services for pain, including prescription-level analgesics, and were more likely to have an endometriosis reoperation. We recommend that future study should aim to better understand the direction of this association between depression and/or anxiety and increased health services use.